Anticandidal activity of some plant extracts - Das, Aparna (Current Botany, 2023)
Candidiasis, especially by Candida albicans is the most prevalent disease over the years. To control the infection, several synthetic drugs and their formulations have been applied. Although antifungals are quite effective in treating candidiasis, long term use has been reported to have side effects. Nevertheless, it has other drawbacks such as efficiency as well as cost, recurrence of the infection, emergences of resistant strains etc. Thus, plant based natural compounds are being investigated for their antifungal activity. In the present study, five different plant extracts assessed exhibited retardation of growth and protease production (molar concentration) in C. albicans. The mycelia form of the organism showed growth resistance to tested plant extracts than the yeast extract form which conferred the higher pathogenicity of the mycelia form. The minimum inhibitory concentration (MIC) of each plant extract was experimentally evidenced with the oil obtained from the seeds of Pongamia glabrata showed the MIC values at the lowest concentration (20-30 μL/mL), followed by seed oil of Azadirachta indica and Ricinus communis. The order of candidostatic efficacy of the various oils was observed to be: Pongamia > Azadirachta > Ricinus > Eucalyptus > Curcuma. These findings have paved the way for further investigation of plant based antifungal agents and their clinical appropriateness for the treatment of Candidiasis.